Formation and Modulation of Nanotubular Assemblies of Oligourea Foldamers in Aqueous Conditions using Alcohol Additives. Issue 10 (22nd July 2020) - Yoo, Sung Hyun; Collie, Gavin W.; Mauran, Laura; Guichard, Gilles
Abstract: There is considerable interest in the rational design of controllable, bioinspired supramolecular systems as a potential means to create new biocompatible and functional materials able to mimic and build upon the characteristics of natural biopolymers. Here, the alcohol‐controlled aqueous self‐assembly of an amphiphilic helical oligourea foldamer (artificial folded oligomer) into a diverse array of tubular fibril architectures is reported. Electron microscopy studies provide details of the morphological evolution of the foldamer nanostructures from protofibrils to fibers, with high resolution X‐ray crystal structures providing an atomic‐scale view of these assemblies, and solution studies indicating the assembly and morphology to be affected by alcohol polarity and concentration. Overall, the results reported here highlight oligourea foldamers as suitable building blocks for the formation of a diverse range of tubular morphologies in a controllable manner. Abstract : Controlled fibrous growth : Oligourea foldamer self‐assembly under the control of alcohol additives. Using a combination of electron microscopy, X‐ray crystallography and circular dichroism, we show that it is possible to control the shape and morphology of tubular assemblies formed from an oligourea foldamer – from single short tubules to extended tubule bundles (i.e. fibres) – by modulating the polarity of the aqueous environment through the use of alcohol additives.